Mozambique [in Strategies and priorities for African agriculture] - Thurlow, James (International Food Policy Research Institute, 2012)
After emerging from civil war in 1994 as one of the world’s poorest countries, Mozambique has since become one the world’s fastest growing countries. Gross domestic product (GDP) grew at 8 percent per year during 1996– 2003 while the national poverty rate fell from 69 to 55 percent (World Bank 2010). Much of this poverty reduction occurred in rural areas, where a rebound in agricultural production led to large improvements in household incomes and food security. However, even though the economy has continued to grow at more than 7 percent during 2003–09, the benefits to the poor have diminished. The national poverty rate remained virtually unchanged during this period (Mozambique, MPD 2010), mainly because of the poor performance of the agricultural sector and the effects of the 2008 food price crisis on urban households (see Arndt et a. 2008, 2010)